Rediseño de rótulos de peluquerías del cantón Latacunga barrio La Merced. - Laica Alvarez, Mónica Silvana (2019)
The research project allowed to enter into the problem of indifference in expert graphic design for the creation of identifying signs for small businesses in popular neighborhoods. Many of them characterized by diffuse designs, diffuse composition, lack of chromatic harmonies, absence of quality in photography, typography, chromatic and limited visual ergonomics that allow readability and condition. The research proposed redesign the signs of hairdressers in the neighborhood "La Merced" to improve the identification and image of the business. The information was obtained through interviews with the owners of hairdressing salons and beauty salons, which allowed us to prepare a location map for this type of business. As instruments of data collection, a first questionnaire was applied to the places that offer these services in La Merced neighborhood of Latacunga city. At the end, all the owners were interviewed and from them a sample of hairdressers willing to participate in the research was obtained, with two locations participating in the Aliry's and Fantasies Nails project. Once the two hairdressers were selected, the use of the "Graphic Design Thinking" methodology of Ellen Lupton (2012), it was considered in his work intuition, action and creation. This methodology divided into three phases: identification of the problem, generation of ideas, and definition of the form. From this, we obtained guidelines to create creative graphics based on qualitative and visual research. A second interview guide allowed to prepare a brief, which includes the needs of the sign design, thanks to the research techniques, the opinion of the owners of the hairdressing salons of La Merced district was obtained, obtaining qualitative data that allowed to realize the graphic construction. As a result, the style guide was obtained for the redesign of these signs, obtaining a renewed and current image for the commercial premises. Through this project he made models of the new commercial signs for the hairdressers Aliry's and Fantasies Nails. It is expected that as a technical impact, the present project will serve as a reference for future projects, since it serves as an example for the development and use of this methodology in other hairdressing salons